2017
DOI: 10.1007/s00122-017-2891-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and genetics of multiple soybean aphid biotype resistance in five soybean plant introductions

Abstract: Five soybean plant introductions expressed antibiosis resistance to multiple soybean aphid biotypes. Two introductions had resistance genes located in the Rag1, Rag2, and Rag3 regions; one introduction had resistance genes located in the Rag1, Rag2, and rag4 regions; one introduction had resistance genes located in the Rag1 and Rag2 regions; and one introduction had a resistance gene located in the Rag2 region. Soybean aphid (Aphis glycines Matsumura) is the most important soybean [Glycine max (L.) Merr.] inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Both genes belong to the coiled-coil nucleotide-binding site-leucine-rich repeat (CC-NBS-LLR) class of resistance genes. Other aphid resistance genes have been identified, but not yet isolated, such as the Rag resistance genes in soybean ( Glycine max ) against the soybean aphid ( Aphis glycines ) (Hill et al , 2017; O’Neal et al , 2018) and the Dn resistance genes in wheat ( Triticum aestivum ) against the Russian wheat aphid ( Diuraphis noxia ) (Botha et al , 2014). The Ra gene in lettuce, which confers resistance to the lettuce root aphid ( Pemphigus bursarius ), has also been shown through reverse genetics to be a member of the NLR family, contained within a large R gene cluster (Wroblewski et al , 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Both genes belong to the coiled-coil nucleotide-binding site-leucine-rich repeat (CC-NBS-LLR) class of resistance genes. Other aphid resistance genes have been identified, but not yet isolated, such as the Rag resistance genes in soybean ( Glycine max ) against the soybean aphid ( Aphis glycines ) (Hill et al , 2017; O’Neal et al , 2018) and the Dn resistance genes in wheat ( Triticum aestivum ) against the Russian wheat aphid ( Diuraphis noxia ) (Botha et al , 2014). The Ra gene in lettuce, which confers resistance to the lettuce root aphid ( Pemphigus bursarius ), has also been shown through reverse genetics to be a member of the NLR family, contained within a large R gene cluster (Wroblewski et al , 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Previous laboratory tests have shown that these two resistant varieties present more challenging environments for the Ap. glycines to colonize and thrive on than Rag2 (Ajayi-Oyetunde et al, 2016;Hill et al, 2017).…”
Section: Response To Rag Resistant Varietiesmentioning
confidence: 98%
“…These findings showed that the soybean aphid possessed potentially significant genetic variability that resulted in virulence, posing a threat to the durability of plant host resistance used to manage this pest. This knowledge prompted soybean breeders to expand their search for new host resistance sources (Hill et al, 2017) and develop genetic strategies to improve the durability of host resistance genes, such as pyramiding multiple resistance genes together within soybean cultivars (McCarville et al, 2014;Ajayi-Oyetunde et al, 2016), to retard the adaptation to host resistance and slow the erosion of resistance efficacy. Multiple Rag genes have been mapped in soybean and several commercial varieties with Rag1, Rag2 and Rag1+2 are commercially available (McCarville et al, 2014;Hesler et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The major loci were located on chromosome 7 ( qChrom.07.1 ) (1Mb distant from Rag1 ) and chromosome 16 ( qChrom.16.1 ) (near Rag3 ); the minor loci were located on chromosome 13 ( qChrom.13.1 ) (near Rag4 ) and chromosome 17 ( qChrom.17.1 ) and were associated with aphid resistance in PI603712. Hill, et al [71] characterized multiple SBA biotype resistances in five cultivars.…”
Section: Soybean Aphidmentioning
confidence: 99%